Strategi Advokasi Anti Diskriminasi sebagai Solusi Perlindungan terhadap Kelompok Rentan Albino - Mawadda, Nurul; Dewanti, Andi Putri; Alfarabi, Andi Ahmad; Aisyah, Nurul; Mubarak, Nurfitah Ersya; Andi Sapiddin, Andi Syahwiah (Universitas Ekasakti, 2023)
In addressing the issue of discrimination against albino individuals, a specific and comprehensive approach and strategy are needed to prioritize human rights protection principles such as equality, equity, mutual respect, and inclusivity among individuals. This approach is known as